(untitled) (Nexo Revista Científica, 2018)
The principal microbiological indicators of the water quality for human consumption were determined by means of the most probable number (NMP) and the isolation joined identification by morphologic and molecular route of the microorganisms isolated from existing biofilm in the point of capture of the aquifer of the community El Cacao, city council Mozonte, Nueva Segovia. Sampling in 3 points: capture, storage and key of jet, and realizing analysis of the NMP, isolations, purification and morphologic tests in the laboratories of the National Program of Investigation Studies and Environmental Services (PIENSA) from National University of Engineering. The microbial sequences were in charge to Molecular Biology of the Central American University. The results indicate pollution by total coliforms, fecal and E.coli, which should be absent according to the norm of The Regional Committee of Institutions of Drinkable Water and sanitation of Central America, Panama and Dominican Republic (CAPRE). Bacterial were isolated from biofilm and identified as: Alcaligenes sp, Paenalcaligenes sp, Alcaligenes faecalis, Paenalcaligenes suwonensis, Proteus mirabilis, Serratia nematodiphilia and Stenotrophomona maltophilia. Filamentous fungi like Apergillus terreus and three isolated identified as aspergillus sp. These microorganisms have been reported in charge of diverse diseases transmitted by the water.